Die kerklike hantering van eietydse transformasieprosesse deur die bedryf van "n arbeidspsigologiese nywerheidsbedieningsmodel - Pieterse, Hennie J. C. (HTS teologiese studies, 2011)
The utilising of a Christain workpsychological industrial church mission to address the modern transformation processesThe church reacted unsatisfactoraly to both political and industrial change. This situation neccessitated the development of a workpsychological industrial mission. This model combines the different industrial mission models, the structure and system of Industrial Mission in South Africa (IMSA) and the German workpsychological approach. The main aim is self-development and self-actualisation. The implication of the model is through Scripture ministry with a special focus on social ethics and a worktheology. The second leg is pastorale care which implements the employee assistant programs (EAP) of companies and adresses the work, personal and environmental problems of all gender, religion and cultural groups from a Christian perspective. The failure of the church to utilise the industrial mission to the full results in a loss for the church’s ministry during transformation.